Updates of Empirical Estimates of Marxian Categories: The Philippines 1961–2012 - Venida, Victor S. (Archīum Ateneo, 2020)
The economies of developing countries have a dualist structure in which feudal and capitalist modes coexist and interact. For the Philippines, this dualism is evident. This paper analyzes the Philippines’s economic structure through a theoretical framework that draws on a Marxian theory interpreted by Wolff (1977, 1979): the model of social disarticulation and the creation of relative surplus value. Adding on to estimates for 1961–2000 for further analysis, this paper updates the estimated Marxian categories for the Philippines using the Input-Output tables from 1961 to 2012 and the formal model used by Venida (2007, 2011). Results of the estimates show labor productivity improvements from 2000 to 2012, which point to the possibility that the Philippine economy could have begun to transition to further capitalist expansion.